Campaign Strategy for the Election of Bojongmalaka Village Head, Baleendah District, Bandung Regency in 2022 - Rudiansah, Bambang; Winangsih, Wiwin; Anugrah, Bilal Maulana; Purnama, Nabil; Wulansari, Anggi Agustini; Dewanti, Salma; Suhendar, Iqbal Maulana; Ramadhan, Gema; Lukmansyah, Lucky; Tsugumol, Fenny Antonia (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study aims to analyze the campaign strategies implemented in the village head election of Bojongmalaka, Baleendah District, Bandung Regency, in 2022. The village head election is a democratic process that involves active community participation in choosing local leaders who will influence village development. This study uses a qualitative approach with a case study method, involving in-depth interviews with candidates, campaign teams, and local residents, as well as analysis of campaign-related documents. The results of the study indicate that an effective campaign strategy includes several key elements, including good candidate introduction, optimal use of social media, a personal approach through direct visits to residents' homes, and delivery of work programs that are relevant to the needs of the village community. Factors such as candidate popularity, support from community leaders, and mass mobilization also play a significant role in determining election results. These findings provide insight into local political dynamics and can be a guide for candidates in similar elections in the future.